The Effect Of Coconut Water Consumption On Labor Advancement In The Phase I Activities In The Mother - Wardhani, Ratih Kusuma; Ernawati, Endah; Dinastiti, Vide Bahtera (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Prolonged labor can increase abnormalities in the physiology of labor and increase the number of labor with cesarean section. Efforts in overcoming the progress of labor are hampered by caring for the mother in the labor process, including giving freedom to the mother to eat or drink as long as the mother wants to need fulfill her nutrition. This research was Analyze the effect coconut water consumption to advancement labor of active process phase I to intranatal. Design was used quasy experimental with One group pre and post test technique. Data was analyzed with Mann-Whitney. Result showed that there was p-value 0,043 < α (0,05) so There was a significant influence of the provision of coconut water on the progress of labor in the first stage. There are correlation coconut water on average accelerates the opening by 54 minutes.